ANALYSIS OF FACTORS AFFECTING THE SELLING PRICE OF FROZEN BIG EYE TUNA (TUNNUS OBESUS) AT CILACAP FISHING PORT - Shalichaty, Shiffa Febyarandika; Saputra, Suradi Wijaya; Wijayanto, Dian; Surarso, Bayu (Jurnal Segara, 2025)
Bigeye tuna is one of Indonesia's leading fishery commodities. One of the main locations for the routine landing and handling of this species is the Cilacap Fishing Port. The selling price of bigeye tuna plays a crucial role in the sustainability of fisheries businesses. However, unstable and unpredictable tuna prices make it difficult for some businesses to assess their long-term sustainability. Various factors influence tuna prices, both internal to fishing operations and external economic conditions. This study aims to identify factors that influence the selling price of bigeye tuna at the Cilacap Fishing Port. This study used direct observation, interviews, and a literature review, with data ranging from 2022 to 2024. The analytical approach used was multiple linear regression analysis. The research findings indicate that the selling price of frozen bigeye tuna is influenced by production volume, production value, fishing month, and operational costs. The F-test results indicate that the dollar exchange rate, export volume and value, production volume, production value, fishing month, and operational costs simultaneously influence the selling price of bigeye tuna. These variables influence 80.6% of the selling price of bigeye tuna, while 19.4% is influenced by other factors outside the research.